2007
DOI: 10.1139/b07-105
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical natural hybridization betweenPopulus deltoidesandP.balsamifera(Salicaceae)This note is one of a selection of papers published in the Special Issue on Poplar Research in Canada.

Abstract: Natural hybridization has long been recognized as a means for gene flow between species and has important evolutionary consequences. Although hybridization is generally considered to be symmetrical, with both hybridizing species being equally likely to be the male or female parent, several studies have demonstrated the presence of asymmetrical hybridization and introgression from one species to the other. We investigated the direction of natural hybridization between two sympatric forest tree species in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Developing cost-effective, efficacious molecular markers to reliably distinguish species and their hybrids is an important first step to enable studies of systematics, taxonomy, population genetics, and evolutionary ecology. Contemporary molecular genetics approaches that take advantage of the P. trichocarpa genome sequence are shedding new light on hybridization in Populus and gene flow between species and populations, as described in Meirmans et al (2007) and Hamzeh et al (2007). In their article, Temmel et al (2007) also take advantage of the genome sequence to examine the genomic region in P. trichocarpa that corresponds to a putatively sex-linked locus in Salix.…”
mentioning
confidence: 99%
“…Developing cost-effective, efficacious molecular markers to reliably distinguish species and their hybrids is an important first step to enable studies of systematics, taxonomy, population genetics, and evolutionary ecology. Contemporary molecular genetics approaches that take advantage of the P. trichocarpa genome sequence are shedding new light on hybridization in Populus and gene flow between species and populations, as described in Meirmans et al (2007) and Hamzeh et al (2007). In their article, Temmel et al (2007) also take advantage of the genome sequence to examine the genomic region in P. trichocarpa that corresponds to a putatively sex-linked locus in Salix.…”
mentioning
confidence: 99%
“…Intersectional hybridization plays an important role in the genetic improvement of the species of the genus Populus and wide hybridization easily contributes to hybrid incompatibility and hybrid sterility, but it is a way to produce transgressive hybrids. Cross-incompatibility usually occurs in wide hybridization and it generally takes place as the dropping of flowers and fruits, low seed set, shriveled seeds, and low seed formation percentage [66][67][68]. In our study, the combinations which had P. deltoides as the male parent had a low seed formation percentage and seed set, shriveled seeds, and low seed germination rate, some having no collected seed.…”
Section: Discussionmentioning
confidence: 61%
“…Meanwhile, Mahama et al [68] pointed out that the crosses involving male P. deltoides and female P. maximowiczii were less successful and rarely acquired seedlings. However, when P. deltoides was taken as the female and some species of section Tacamahaca were taken as male, the crosses showed a high success rate, obtaining many seedlings [33,66,67]. The results in our research suggested that cross-incompatibility was occurring.…”
Section: Discussionmentioning
confidence: 69%
“…Adding to this complexity, trihybrids (crosses involving three different species) and more complex combinations have been developed and deployed in Populus-breeding programs (e.g., Meirmans et al 2010;Talbot et al 2011) and have been detected in nature (Thompson et al 2010;Talbot et al 2012;Williams et al, unpublished). Molecular diagnostics, including AFLP (Cervera et al 2005), DNA sequencing (Hamzeh and Dayanandan 2004) combined with RFLP , microsatellites (Liesebach et al 2010), and mediumthroughput single nucleotide polymorphism (SNP)-based genotyping assays (Hamzeh et al 2007;Meirmans et al 2007; Thompson et al 2010;Talbot et al 2011) have been used to diagnose poplar species and hybrids with success.…”
Section: Introductionmentioning
confidence: 99%